Brinjal (Solanum melongena) Fruit Yield in Response to Urea Super Granule Application (The Agriculturists, 2010)
Experiments were conducted to assess the effects of USG on the number of branch and fruit production, fruit length, weight and yield of brinjal (Solanum melongena: cv Shingnath), compared to prilled urea as N source. The study was conducted at farming systems research and development site, Palima, Tangail district under AEZ 8 of Bangladesh during 2000, 2001 and 2002 using randomized complete block design (RCBD) with five treatments replicated 6 times. The treatments were T1= N78P36K66S17CD3t (Recommended dose for high yield goal (HYG), N as prilled urea), T2= N78P36K66S17CD3t (Recommended dose for HYG, N as USG), T3= N65P36K66S17CD3t (N 10%< Recommended dose as USG), T4= N52P36K66S17CD3t (N 20%